Preparation process of 3D curved glass

By combining various components, using clarification agents and crystallization treatment, 3D curved glass with excellent mechanical properties and impact resistance was prepared, which solved the problems of glass being easily broken, scratching and visual distortion in the prior art, and achieved a uniform and stable display effect.

CN119774878AActive Publication Date: 2025-04-08DONGGUAN YIPIN GLASS TECH CO LTD

Patent Information

Application Number
CN202411954333.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing 3D curved glass is prone to shatter when impacted by external forces, the surface is soft and easy to scratch, and the refraction and reflection of light lead to visual distortion, affecting the display effect.

Method used

By combining components such as boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide, combined with clarification agent and crystallization treatment, 3D curved glass with excellent mechanical properties, strong impact resistance and uniform display were prepared.

Benefits of technology

The mechanical performance of 3D curved glass has been improved, impact resistance is enhanced, and display uniformity is improved, deformation and distortion are avoided, and the overall performance of the glass is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215530150000121
    Figure BDA0005215530150000121
Patent Text Reader

Abstract

The invention relates to the technical field of glass, in particular to a preparation process of 3D curved glass. The process comprises the following steps: S1, mixing diboron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide, grinding, sieving, uniformly mixing, and heating to obtain a liquid phase substance; s2, clarifying the liquid-phase substance, introducing the clarified liquid-phase substance into a mold cavity, and carrying out hot bending forming to obtain a crude blank; and S3, annealing the rough blank, and carrying out fine trimming to obtain the 3D curved glass. The curved glass provided by the invention is excellent in mechanical property, high in impact resistance, uniform in display and free of deformation and distortion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass, and in particular relates to a preparation process of 3D curved glass. Background Art

[0002] Curved glass refers to glass with a curved surface that can form various curvatures and curves in two-dimensional or three-dimensional space. The curvature can be single or multi-curvature, thus giving the product a unique look and feel. Common curved glass can be divided into 2D curved glass, 2.5D curved glass and 3D curved glass. 2D curved glass has a curvature only on one plane; 2.5D curved glass is based on flat glass, with the edges polished to a certain curvature, so that the edges appear curved; 3D curved glass refers to glass with a curved design in the middle and edges, presenting a complex three-dimensional curve in three-dimensional space. Widely used in smart phones, tablets, smart watches and other devices, curved glass as a screen cover or shell can not only provide better visual effects and touch experience, but also make the product thinner and more beautiful, thereby enhancing product competitiveness and added value. In the lenses of virtual reality (VR) / augmented reality (AR) devices, smart glasses, etc., curved glass can better fit the curve of the human face, provide a wider field of view and a comfortable wearing feeling, while also helping to achieve miniaturization and lightweighting of the device. Curved glass is widely used.

[0003] Despite the strengthening treatment, the brittleness of the glass itself still exists. Due to its special shape and large area, curved glass is more likely to break when impacted by external forces. Moreover, its surface is relatively soft and easily scratched by hard objects such as metal and sand, which affects its appearance and usability. In addition, curved glass refracts and reflects light, causing visual distortion. When displaying images or text, there may be deformation and distortion, which affects the viewing effect.

[0004] For example, CN117776536A discloses a 3D curved glass-ceramic, a chemically strengthened glass-ceramic, and a preparation method and application thereof. In terms of the molar percentage of oxides, the composition of the 3D curved glass-ceramic satisfies:

[0005] 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250;

[0006] 18.200≤Li2O / P2O5≤25.500;

[0007] 0.100≤P2O5×(CaO+ZrO2+Li2O+A l2 O3) / (Na2O+K2O+B2O3)≤2.20;

[0008] 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000;

[0009] 4.000≤(SiO27Al2O3Li2O) / (P2O5+ZrO2)≤6.000.

[0010] The oxides work synergistically to achieve the goal of uniform display, but the aluminum oxide content is too high. It is a typical crystal structure oxide and does not have a good crystal plane to disperse the impact force, so the glass is more brittle.

[0011] For example, CN114538773A discloses a borophosphate luminescent glass doped with a rare earth element Sm and a preparation method thereof, wherein the raw materials of the luminescent glass are composed of P2O5, H3BO3, CdF2, ZnO, and MgO, wherein P2O5 is 5-15%, H3BO3 is 5-60%, CdF2 is 1-10%, ZnO is 10-20%, and MgO is 5-15%; the rare earth oxide is Sm2O3, and the mass percentage is 0.05-2%. The application uses the rare earth element Sm as a luminescent agent to prepare borophosphate luminescent glass, which is mainly used in the field of orange-red lasers. However, it is difficult to achieve an ideal distribution uniformity in the glass by simply adding Sm ions, and local enrichment or concentration gradients are prone to occur. This will lead to differences in the refractive index of different parts of the glass, thereby affecting the stability of the overall refractive index of the glass, and further reducing the optical quality and performance of the glass.

[0012] In view of this, the present invention is proposed. Summary of the invention

[0013] The purpose of the present invention is to provide a preparation process of 3D curved glass. The curved glass provided by the present invention has excellent mechanical properties, strong impact resistance, and its display is uniform without deformation or distortion.

[0014] In order to achieve the above object, the present invention provides the following technical solutions:

[0015] In a first aspect, an embodiment of the present invention provides a process for preparing 3D curved glass, comprising the following steps:

[0016] S1, mixing boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide, grinding and sieving the mixture to obtain a liquid phase after heating;

[0017] S2, clarifying the liquid phase, draining the clarified liquid phase into a mold cavity, hot bending and forming, and obtaining a rough blank;

[0018] S3, annealing the rough blank and obtaining the 3D curved glass after fine finishing.

[0019] The present invention compounds a plurality of rare earth oxides, and the glass is colorless after compounding. The mechanical properties of the glass are improved by adjusting the ratio of the rare earth oxides to boron trioxide, ammonium dihydrogen phosphate, lithium oxide and calcium carbonate. The glass is uniform in display and will not be deformed or distorted.

[0020] This is mainly because boron trioxide is a glass network former, which can form a network structure with other components in the glass. In glass, boron atoms can combine with oxygen atoms to form two coordination structures, [BO] and [BO]. [BO] is a planar triangular structure, and [BO] is a tetrahedral structure. This structure can enhance the network strength of the glass and make the structure of the glass denser, thereby improving the mechanical properties of the glass such as hardness and elastic modulus. In addition, boron trioxide can reduce the thermal expansion coefficient of the glass. When the temperature of the glass changes, a small thermal expansion coefficient means that its volume changes little, and the internal stress generated during the temperature change process is also small, which helps to improve the thermal shock resistance of the glass and indirectly enhances the mechanical stability of the glass. The added ammonium dihydrogen phosphate will decompose during the glass melting process to produce ammonia (NH) and phosphoric acid (HPO). The escape of ammonia will leave tiny pores in the glass. Appropriate pores can play a buffering role, absorb a certain amount of energy, and improve the toughness of the glass. And phosphorus element can enter the glass network structure formed by boron trioxide to form PO bond, the existence of this bond can change the network structure of glass, increase the crosslinking degree of network, improve the hardness and flexural strength of glass, and also contribute to the chemical stability of glass, indirectly have a positive impact on mechanical properties. And lithium oxide is an effective flux, it can reduce the melting temperature of glass, and the melting point of the composite multiple rare earth oxides of the present invention itself is higher, so that glass can be melted and formed at a lower temperature after reducing the melting point. And in the glass structure, lithium ions can be filled in the gap of the glass network, play a disconnection effect, and make the glass network structure loose. This structural change can reduce the hardness of glass to a certain extent, but also can increase the toughness of glass, make it not easy to brittle fracture, improve its impact resistance, more importantly, lithium oxide can improve the thermal stability of glass, reduce the internal stress generated by glass when temperature changes, thereby improve the thermal shock resistance of glass. Similarly, the added calcium carbonate can be decomposed into calcium oxide (CaO) and carbon dioxide (CO) during glass melting. Calcium oxide can be used as a glass network modifier, and it can be combined with the glass network structure formed by boron trioxide, increase the connectivity of the glass network, and improve the hardness and strength of the glass. At the same time, the escape of carbon dioxide also forms some tiny pores in the glass, to increase the sound absorption, heat insulation and other properties of the glass, and to a certain extent improves toughness and improves its impact resistance. In addition, in processes such as annealing and cooling, the calcium oxide added by the present invention promotes the formation of crystal nuclei, causing crystallization in the glass. Appropriate crystallization can improve the mechanical properties of the glass, such as making the glass more compact, and increasing hardness and strength. And the effect of the composite rare earth oxide of the present invention in molding is even more closely indispensable, first cerium oxide can play the role of a clarifier in the glass melting process, and it can reduce the viscosity of the glass melt, promote the discharge of bubbles, and make the glass more uniform.The uniform glass structure helps to improve the mechanical properties of glass, because the bubbles formed by ammonium dihydrogen phosphate and calcium carbonate are within a controllable range, avoiding stress concentration caused by defects such as bubbles and impurities, and the strength and toughness of the glass can be guaranteed. In addition, cerium oxide can improve the chemical stability of glass and reduce the corrosion and degradation of glass in the environment. Samarium oxide can enter the network structure formed by boron trioxide and interact with other ions in the glass, enhance the connection strength and tightness of the glass network, increase the density and hardness of the glass, and when the glass is impacted by external force, the samarium ions will absorb part of the energy and dissipate the energy through processes such as its electronic transition. This energy absorption mechanism can improve the impact resistance of glass to a certain extent, making the glass less likely to break when impacted. Similarly, ytterbium oxide can be used as a glass network modifier. After ytterbium ions enter the glass network, they will form chemical bonds with other ions, making the glass network tighter and improving the hardness and elastic modulus of the glass. At the same time, ytterbium oxide can also improve the wear resistance of glass and make the glass surface more wear-resistant. In addition, the compounded rare earth oxides of the present invention can avoid the color development effect of a single rare earth oxide, such as the light blue of ytterbium oxide, the light yellow of cerium oxide, and the slightly yellowish white of samarium oxide. In the principle of color mixing, yellow is red and green, and the compounding of red, green and blue can obtain white, that is, transparent.

[0021] In addition, the composite rare earth oxide of the present invention can improve the display uniformity of glass by controlling the optical constants of glass, improving the purity and uniformity of glass, and enhancing the radiation resistance and weather resistance of glass.

[0022] In terms of controlling the optical constants of glass, cerium oxide has a higher refractive index, which can change the refractive index of glass to make it more compatible with the refractive index of surrounding glass, reduce the scattering and refraction of light inside the glass, thereby improving the optical uniformity of the glass and improving the reflection uniformity. Samarium oxide can adjust the refractive index and dispersion of glass to a certain extent, so that the glass has more uniform reflection and refraction characteristics for light of different wavelengths, which helps to improve the reflection uniformity of glass in the visible spectrum. In addition, ytterbium oxide also has a certain regulating effect on the refractive index of glass, which can make the optical properties of glass more stable and uniform, and reduce the uneven reflection of light caused by differences in refractive index. The three rare earth oxides compounded in the present invention make the formed curved glass uniform.

[0023] In terms of improving the purity and uniformity of glass, cerium oxide is used as a glass clarifier. During the glass melting process, cerium dioxide decomposes oxygen at high temperature, which can oxidize impurities in the glass, reduce glass coloring, improve the transparency and purity of the glass, and facilitate the uniform transmission and reflection of light, thereby improving the reflection uniformity of the glass. Samarium oxide has high chemical stability and purity, and is not easy to introduce impurities during the glass preparation process, which helps to improve the overall purity and uniformity of the glass and provide a basis for achieving good reflection uniformity. Ytterbium oxide can refine the grains of glass, inhibit the abnormal growth of grains during the preparation process of glass, and make the microstructure of the glass more uniform, thereby improving the optical uniformity and reflection uniformity of the glass.

[0024] In terms of enhancing the radiation resistance and weather resistance of glass, cerium oxide has good ultraviolet absorption ability, which can absorb ultraviolet rays and convert them into heat energy to dissipate, reduce the damage of ultraviolet rays to glass, improve the anti-ultraviolet performance of glass, protect the stability of the internal structure of glass, and help maintain the uniformity of glass reflection performance. Samarium oxide can absorb infrared rays, reduce the thermal effect of infrared rays on glass, reduce the expansion and contraction unevenness of glass caused by temperature changes, thereby improving the dimensional stability and reflection uniformity of glass. Ytterbium oxide can improve the chemical corrosion resistance and oxidation resistance of glass, enhance the stability of glass under different environmental conditions, prevent the change of reflection performance of glass surface due to erosion by external factors, and ensure the long-term stability of glass reflection uniformity.

[0025] In a preferred embodiment, in step S1, the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide is (50-70): (5-10): (10-30): (5-10): (1-3): (1-3): (2-6).

[0026] In a preferred embodiment, in step S1, the ground mixture is passed through a 300-500 mesh screen.

[0027] In a preferred embodiment, in step S1, the heating temperature is 1000-1200°C, and the heating time is 1-4h.

[0028] In a preferred embodiment, in step S2, the clarification is performed using a clarifier, the mass ratio of the added amount of the clarifier to the liquid phase is 1:(30-60), the clarifier comprises a mixture of cerium oxide, calcium fluoride and sodium chloride, and the mass ratio of the cerium oxide, calcium fluoride and sodium chloride is 1:(1-2):(1-2).

[0029] In a preferred embodiment, the preparation method of the clarifier is as follows:

[0030] Cerium oxide, calcium fluoride and sodium chloride are calcined at 800-1000°C for 2-4 hours to obtain a clarifier.

[0031] The compounded clarifier of the present invention further ensures the shortcomings of many bubbles and high viscosity in the compounded curved glass of the present invention, wherein calcium fluoride and sodium chloride can reduce the viscosity of the glass melt. When the two are used at the same time, the effect of reducing viscosity can be superimposed on each other, so that the viscosity of the melt is lower, and the lower viscosity provides more favorable conditions for the discharge of gas impurities, so that the gas can escape from the melt more quickly and smoothly, greatly improving the clarification efficiency. Cerium oxide releases oxygen to oxidize impurities to produce carbon dioxide, while sodium chloride and calcium fluoride reduce viscosity to promote gas discharge. In addition, the volatile gas produced by the reaction of calcium fluoride and the volatile impurity salts formed by sodium chloride, together with the carbon dioxide produced by cerium oxide, can be more effectively discharged from the glass melt in a low-viscosity melt environment, making the glass more clarified. The stable oxidizing environment provided by cerium oxide, the adjustment of the glass network structure by calcium oxide generated by calcium fluoride, and the potential influence of the dissociated ions of sodium chloride on the glass structure, the synergistic effect of the three can enable the glass to maintain good structural stability during the clarification process. The stable structure helps to prevent new gas impurities from entering the interior of the glass, and is also conducive to the glass maintaining good quality and optical properties after clarification.

[0032] In a preferred embodiment, in step S2, the specific steps of the hot bending forming are:

[0033] The liquid phase is kept warm at 800°C-900°C for 1-2 hours under a pressure of 0.1-0.4Mpa to obtain a rough embryo.

[0034] In a preferred embodiment, in step S3, the rough blank needs to be crystallized before annealing.

[0035] In a preferred embodiment, the specific steps of the crystallization treatment are:

[0036] The rough blank is cooled to release the thermal stress to room temperature at a cooling rate of 1-3°C / min, and then the rough blank is heated to 400-600°C at a heating rate of 2-5°C / min and kept at this temperature for 2-4h to obtain the rough blank after crystallization treatment.

[0037] In the present invention, the rough blank is subjected to crystallization treatment, thereby enhancing the mechanical properties and thermal stability of the glass, and the distribution of the components after crystallization is more uniform, thereby enhancing the transparency and glossiness of the glass.

[0038] During the crystallization process, boron trioxide can provide a suitable infrastructure for the crystallization of other substances, which helps to form a more regular and stable crystal phase structure. The crystal structure of cerium oxide is a fluorite structure with cubic symmetry. During the crystallization of glass, this stable structure of cerium oxide can serve as a crystal nucleus to induce other components in the glass to crystallize around it, promote the crystallization process, improve the crystallization efficiency, and also enhance the overall structural stability of the glass. After the crystallization treatment, samarium oxide and ytterbium oxide ions will enter the lattice of the glass, causing lattice distortion, thereby increasing the complexity and stability of the glass structure. This lattice distortion can hinder the movement of dislocations, making it more difficult for the glass to deform and break, and improving its mechanical strength and thermal stability.

[0039] In a preferred embodiment, in step S3, the specific steps of annealing are:

[0040] The rough blank is cooled to release the thermal stress to room temperature, and the cooling rate is 1-3℃ / min.

[0041] In a second aspect, an embodiment of the present invention provides a 3D curved glass obtained by the above-mentioned preparation process of 3D curved glass.

[0042] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0043] 1. The present invention compounds a variety of rare earth oxides. After the compounding of the present invention, the color of the glass is colorless. The mechanical properties of the glass are improved by the ratio of the rare earth oxides to boron trioxide, ammonium dihydrogen phosphate, lithium oxide, and calcium carbonate. The glass is uniform in display and will not be deformed or distorted.

[0044] 2. The rare earth oxides compounded in the present invention can improve the display uniformity of glass by controlling the optical constants of glass, improving the purity and uniformity of glass, and enhancing the radiation resistance and weather resistance of glass.

[0045] 3. The compounded clarifier of the present invention further ensures the shortcomings of many bubbles and high viscosity in the compounded curved glass of the present invention. The stable structure helps to prevent new gas impurities from entering the interior of the glass, and is also beneficial for the glass to maintain good quality and optical properties after clarification.

[0046] 4. The present invention performs crystallization treatment on glass, thereby enhancing the mechanical properties and thermal stability of the glass, and the distribution of the components after crystallization is more uniform, thereby enhancing the transparency and glossiness of the glass. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available.

[0049] Example 1

[0050] This embodiment provides a process for preparing 3D curved glass, comprising the following steps:

[0051] S1, mixing boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide, grinding and mixing evenly after passing through a 300-mesh sieve, wherein the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide is 68.5:8:17:6:2:2:4, heating to 1100°C, and keeping the temperature for 2 hours to obtain a liquid phase;

[0052] S2, clarifying the liquid phase with a clarifying agent. Specifically, the liquid phase and the clarifying agent are mixed and kept at 500° C. for 2 hours. The mass ratio of the added amount of the clarifying agent to the liquid phase is 1:40. The clarified liquid phase is introduced into a mold cavity of the 3D curved glass. The liquid phase is kept at 850° C. for 1 hour under a pressure of 0.1 MPa to obtain a rough blank.

[0053] The preparation method of the clarifier is as follows:

[0054] By weight, 1 part of cerium oxide, 1.5 parts of calcium fluoride and 1.5 parts of sodium chloride were calcined at 900° C. for 3 hours to obtain a clarifier;

[0055] S3, cooling the rough blank to release thermal stress to room temperature, with a cooling rate of 1°C / min, and obtaining the 3D curved glass after fine finishing.

[0056] Example 2

[0057] This embodiment provides a process for preparing 3D curved glass, comprising the following steps:

[0058] S1, mixing boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide, grinding and mixing evenly after passing through a 300-mesh sieve, wherein the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide is 68.5:8:17:6:2:2:4, heating to 1100°C, and keeping the temperature for 2 hours to obtain a liquid phase;

[0059] S2, clarifying the liquid phase with a clarifying agent. Specifically, the liquid phase and the clarifying agent are mixed and kept at 500° C. for 2 hours. The mass ratio of the added amount of the clarifying agent to the liquid phase is 1:40. The clarified liquid phase is introduced into a mold cavity of the 3D curved glass. The liquid phase is kept at 850° C. for 1 hour under a pressure of 0.1 MPa to obtain a rough blank.

[0060] The preparation method of the clarifier is as follows:

[0061] By weight, 1 part of cerium oxide, 1.5 parts of calcium fluoride and 1.5 parts of sodium chloride were calcined at 900° C. for 3 hours to obtain a clarifier;

[0062] S3, cooling the rough blank to release thermal stress to room temperature, the cooling rate is 1°C / min, then heating the rough blank to 500°C at a heating rate of 5°C / min, keeping it warm for 6 hours to obtain the rough blank after crystallization treatment, cooling the rough blank after crystallization treatment to release thermal stress to room temperature, the cooling rate is 1°C / min, and the 3D curved glass is obtained after fine finishing.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 1 is that cerium oxide is not added, and the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, samarium oxide and ytterbium oxide is changed to 68.5:8:17:6:3:5.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 1 is that samarium oxide is not added, and the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide and ytterbium oxide is changed to 68.5:8:17:6:3:5.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 1 is that ytterbium oxide is not added, and the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide and samarium oxide is 68.5:8:17:6:3:3.

[0069] Comparative Example 4

[0070] The difference between this comparative example and Example 1 is that ytterbium oxide, samarium oxide and ytterbium oxide are not added, and the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide and calcium carbonate is 76.5:8:17:6.

[0071] Comparative Example 5

[0072] The difference between this comparative example and Example 1 is that no diammonium phosphate is added, and the mass ratio of boron trioxide, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide is 76.5:17:6:2:2:4.

[0073] Comparative Example 6

[0074] The difference between this comparative example and Example 1 is that lithium oxide is not added, and the mass ratio of boron trioxide, ammonium dihydrogen phosphate, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide is 85.5:8:6:2:2:4.

[0075] Comparative Example 7

[0076] The difference between this comparative example and Example 1 is that calcium carbonate is not added, and the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, cerium oxide, samarium oxide and ytterbium oxide is 74.5:8:17:2:2:4.

[0077] Comparative Example 8

[0078] The difference between this comparative example and Example 1 is that no clarifier is used to clarify the liquid phase.

[0079] Comparative Example 9

[0080] The difference between this comparative example and Example 1 is that the clarifier is changed to cerium oxide.

[0081] Performance Testing

[0082] 1. The impact resistance of the curved glass obtained in the embodiment and the comparative example was tested with reference to GB / T 39814-2021. The falling ball mass was 0.5 kg, 2 kg, and 5 kg. The test was performed 5 times each time to observe the cracking. The results are shown in Table 1.

[0083] 2. The hardness of the curved glass obtained in the embodiment and the comparative example was tested according to the Mohs hardness test method. The results are shown in Table 1.

[0084] 3. Color test: The curved glass obtained in the embodiment and the comparative example and the standard colorless glass sample were placed under the same light source to observe their color development. The results are shown in Table 1.

[0085] 4. The light transmittance of the curved glass obtained in the examples and comparative examples was tested with reference to GB / T 40415-2021. The results are shown in Table 1.

[0086] Table 1 Performance test results

[0087]

[0088] From the above performance test results, it can be seen that the mechanical properties and transparency of Examples 1-2 are the best, especially the impact resistance and light transmittance performance are better, especially the comprehensive performance of Example 2 is the most outstanding, which is mainly due to the synergy of the multiple components and multiple rare earth oxides compounded in the present invention, and the prepared clarifier eliminates the adverse effects of ammonium dihydrogen phosphate and calcium carbonate, and further enhances the strength of the curved glass. The comparative example is significantly worse than the example in the corresponding performance test because it does not adopt the necessary technical solution, which better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.

[0089] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A process for preparing 3D curved glass, characterized in that: The following steps are involved: S1, mixing boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide, grinding and sieving the mixture to obtain a liquid phase after heating; S2, clarifying the liquid phase, draining the clarified liquid phase into a mold cavity, hot bending and forming, and obtaining a rough blank; S3, annealing the rough blank and obtaining the 3D curved glass after fine finishing.

2. The process for preparing 3D curved glass according to claim 1, characterized in that: In step S1, the mass ratio of boron trioxide, ammonium dihydrogen phosphate, lithium oxide, calcium carbonate, cerium oxide, samarium oxide and ytterbium oxide is (50-70): (5-10): (10-30): (5-10): (1-3): (1-3): (2-6).

3. The process for preparing 3D curved glass according to claim 1, characterized in that: In step S1, the ground mixture is passed through a 300-500 mesh screen.

4. The process for preparing 3D curved glass according to claim 1, characterized in that: In step S1, the heating temperature is 1000-1200°C, and the heating time is 1-4h.

5. The process for preparing 3D curved glass according to claim 1, characterized in that: In step S2, the clarification is performed using a clarifier, the mass ratio of the added amount of the clarifier to the liquid phase is 1:(30-60), the clarifier includes a mixture of cerium oxide, calcium fluoride and sodium chloride, and the mass ratio of the cerium oxide, calcium fluoride and sodium chloride is 1:(1-2):(1-2).

6. The process for preparing 3D curved glass according to claim 5, characterized in that: The preparation method of the clarifier is as follows: Cerium oxide, calcium fluoride and sodium chloride are calcined at 800-1000°C for 2-4 hours to obtain a clarifier.

7. The process for preparing 3D curved glass according to claim 1, characterized in that: In step S2, the specific steps of the hot bending forming are: The liquid phase is kept warm at 800°C-900°C for 1-2 hours under a pressure of 0.1-0.4Mpa to obtain a rough embryo.

8. The process for preparing 3D curved glass according to claim 1, characterized in that: In step S3, the rough blank needs to be crystallized before annealing; The specific steps of the crystallization process are: The rough blank is cooled to release the thermal stress to room temperature at a cooling rate of 1-3°C / min, and then the rough blank is heated to 400-600°C at a heating rate of 2-5°C / min and kept at this temperature for 2-4h to obtain the rough blank after crystallization treatment.

9. The process for preparing 3D curved glass according to claim 1, characterized in that: In step S3, the specific steps of annealing are: The rough blank is cooled to release the thermal stress to room temperature, and the cooling rate is 1-3℃ / min.

10. A 3D curved glass obtained by the preparation process of 3D curved glass according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Rare earth element Sm doped borophosphate luminescent glass and preparation method thereof

    CN114538773A

  • 3D curved surface microcrystalline glass, chemically strengthened microcrystalline glass, and preparation method and application of 3D curved surface microcrystalline glass and chemically strengthened microcrystalline glass

    CN117776536A

  • High borosilicate glass clarifying agent, and preparation method and application thereof

    CN106746595A

  • Soluble bactericidal glass and preparation method thereof

    CN114685046A

  • Rare-earth-doped aluminosilicate glasses, especially for use as active laser material in high-power bulk lasers

    DE102013015934A1

Cited By

  • Preparation method of Yb2O3 ceramic core block

    CN118084490A